HOPS Initiates Vacuole Docking by Tethering Membranes before trans-SNARE Complex Assembly - Hickey, Christopher M. (The American Society for Cell Biology, 2010)
Vacuole homotypic fusion has been reconstituted with all purified components: vacuolar lipids, four soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) proteins, Sec17p, Sec18p, the Rab Ypt7p, and the hexameric homotypic fusion and vacuole protein sorting complex (HOPS). HOPS is a Rab-effector with direct affinity for SNAREs (presumably via its Sec1-Munc18 homologous subunit Vps33p) and for certain vacuolar lipids. Each of these pure vacuolar proteins was required for optimal proteoliposome clustering, raising the question of which was most directly involved. We now present model subreactions of clustering and fusion that reveal that HOPS is the direct agent of tethering. The Rab and vacuole lipids contribute to tethering by supporting the membrane association of HOPS. HOPS indirectly facilitates trans-SNARE complex formation by tethering membranes, because the synthetic liposome tethering factor polyethylene glycol can also stimulate trans-SNARE complex formation and fusion. SNAREs further stabilize the associations of HOPS-tethered membranes. HOPS then protects newly formed trans-SNARE complexes from disassembly by Sec17p/Sec18p.